Magnetically recyclable Ni@h-BN composites for efficient hydrolysis of ammonia borane. (22nd June 2017) - Wu, Yawei; Wu, Xin; Liu, Qiuwen; Huang, Caijin; Qiu, Xiaoqing
Abstract: The magnetic Ni@h-BN composites containing the uniform Ni nanoparticles supported on h-BN nanosheets have been prepared via a facile solvothermal method. The as-prepared samples show high catalytic performance for H2 generation from the ammonia borane aqueous solution, especially for the Ni@h-BN with 25.0 wt% Ni content. Moreover, the Ni@h-BN composites possess a good ferromagnetic property at room temperature, endowing them with rapid magnetic separation to recycle. The kinetics of the hydrolysis of ammonia borane over the Ni@h-BN composites were further investigated in detail. It is found that the hydrogen generation was highly dependent on the catalyst amount and the reaction temperature. The activation energy of the hydrolysis reaction of ammonia borane is found to be 47.3 kJ mol −1 over the Ni@h-BN with 25.0 wt% Ni content. Considering the good catalytic activities for H2 release, the Ni@h-BN composites are expected to find important application in fuel cells and the related fields. Graphical abstract: Highlights: The Ni@h-BN catalysts exhibit high catalytic activity and favorable reusability. The Ni@h-BN catalyst shows a good ferromagnetic property at room temperature. The activation energy of the hydrolysis reaction is found to be 47.3 kJ mol −1 .